2-7(x+1)=3(x-2)-5(x+3)

Simple and best practice solution for 2-7(x+1)=3(x-2)-5(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-7(x+1)=3(x-2)-5(x+3) equation:


Simplifying
2 + -7(x + 1) = 3(x + -2) + -5(x + 3)

Reorder the terms:
2 + -7(1 + x) = 3(x + -2) + -5(x + 3)
2 + (1 * -7 + x * -7) = 3(x + -2) + -5(x + 3)
2 + (-7 + -7x) = 3(x + -2) + -5(x + 3)

Combine like terms: 2 + -7 = -5
-5 + -7x = 3(x + -2) + -5(x + 3)

Reorder the terms:
-5 + -7x = 3(-2 + x) + -5(x + 3)
-5 + -7x = (-2 * 3 + x * 3) + -5(x + 3)
-5 + -7x = (-6 + 3x) + -5(x + 3)

Reorder the terms:
-5 + -7x = -6 + 3x + -5(3 + x)
-5 + -7x = -6 + 3x + (3 * -5 + x * -5)
-5 + -7x = -6 + 3x + (-15 + -5x)

Reorder the terms:
-5 + -7x = -6 + -15 + 3x + -5x

Combine like terms: -6 + -15 = -21
-5 + -7x = -21 + 3x + -5x

Combine like terms: 3x + -5x = -2x
-5 + -7x = -21 + -2x

Solving
-5 + -7x = -21 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-5 + -7x + 2x = -21 + -2x + 2x

Combine like terms: -7x + 2x = -5x
-5 + -5x = -21 + -2x + 2x

Combine like terms: -2x + 2x = 0
-5 + -5x = -21 + 0
-5 + -5x = -21

Add '5' to each side of the equation.
-5 + 5 + -5x = -21 + 5

Combine like terms: -5 + 5 = 0
0 + -5x = -21 + 5
-5x = -21 + 5

Combine like terms: -21 + 5 = -16
-5x = -16

Divide each side by '-5'.
x = 3.2

Simplifying
x = 3.2

See similar equations:

| 756x^18= | | (3x+8)=(5x-2) | | y-1=.5x-7 | | 5x+2=4x+2 | | 7(5+n)=42 | | 45x-37y+87-7+3x= | | 12x=29.9 | | 2y-8=y+4 | | 5n+n=3n-2+2(2n+1) | | 2+8lnx=26 | | 24.4-4p=53.3 | | 15+3x+6=-7x+2x+2 | | 12r^2+21r-8r-14=0 | | 2x+2=-5x+23 | | 6x+11=2x+47 | | 16a+3= | | y-5=0x-7 | | p(x)=[x-(1+2i)][x-(1-2i)](x-2)(x+1) | | 3xy+7x+6x+8xy= | | p=-12.5t+100 | | 0.5y+0.2y=0.3y+2 | | 13-1(2x+4)=35 | | 3.1x+2=-0.5 | | 15+-8=x | | 4(2x-3)(4x+5)=0 | | 6(a+2)-2(2a+5)=18 | | 12x^2+24x-288=0 | | (7x+16)+(9x-12)=180 | | 15x+3x=180 | | 9t+-21=3(t+-7)+6t | | 4(3x+1)+4=13x+4 | | 15x-9-4x+9= |

Equations solver categories